Evaluating the Efficacy of a Modified Piezo-Puncture Method on the Rate of Tooth Movement in Orthodontic Patients: A Clinical Study - Maryam Omidkhoda; Mehrdad Radvar; Majid Azizi; Mahboobe Dehghani (Galenos Yayinevi, 2020)
Objective:Owing to the increasing demand from orthodontic patients for a more rapid treatment, many studies have focused on accelerated tooth movement. Currently, one of the prevalent methods to achieve accelerated tooth movement is piezo-puncture. The aim of the present study was to evaluate the effect of a modified piezo-puncture method on tooth movement rate and type during canine retraction.Methods:A total of 17 patients who required fixed orthodontic treatment with extraction of the maxillary first premolars were included in the study. Following a split-mouth design, upper canines were retracted with Ni-Ti coil spring that applied 150 g of force on each side (piezo-puncture on one side and contralateral side served as the control). Then, the rates of tooth movement, canine angulation and rotation, and anchorage loss were evaluated at T0 (before the intervention), T1 (1 month after the intervention), and T2 (2 months after the intervention). For calculating the canine movement rate, either the distance between the canine and the lateral incisor or the space between the second premolar and the canine was measured. In addition, pain perception was documented by Visual Analog Scale. Data were analyzed using the Kolmogorov-Smirnov normality test, Spearman correlation test, paired sample t-test, and Wilcoxon signed-rank test.Results:No significant acceleration was observed in canine movement, canine tipping, rotation, or anchorage loss of molar in different times.Conclusion:Considering the limitations of the study, the application of piezo-puncture employing the protocol used in the present study failed to accelerate tooth movement and to decrease the unfavorable tipping, rotation, and molar anchorage loss.